Effect of Pantethine on Ovarian Tumor Progression and Choline Metabolism - Penet, Marie-France; Krishnamachary, Balaji; Wildes, Flonne; Mironchik, Yelena; Mezzanzanica, Delia; Podo, Franca; de Reggi, Max; Gharib, Bouchra; Bhujwalla, Zaver M. (Frontiers in Oncology, 2016)
Epithelial ovarian cancer remains the leading cause of death from gynecologic malignancy among women in developed countries. New therapeutic strategies evaluated with relevant preclinical models are urgently needed to improve survival rates. Here we have assessed the effect of pantethine on tumor growth and metabolism using magnetic resonance imaging (MRI) and high-resolution proton magnetic resonance spectroscopy (MRS) in a model of ovarian cancer. To evaluate treatment strategies, it is important to use models that closely mimic tumor growth in humans. We therefore used an orthotopic model of ovarian cancer where a piece of tumor tissue, derived from an ovarian tumor xenograft, is engrafted directly onto the ovary of female mice, to maintain the tumor physiological environment. Treatment with pantethine, the precursor of vitamin B5 and active moiety of coenzyme A, was started when tumors were approximately 100 mm3, and consisted of a daily i.p. injection of 750 mg/kg in saline. Under these conditions, no side effects were observed. High-resolution 1H MRS was performed on treated and control tumor extracts. A dual-phase extraction method based on methanol/chloroform/water was used to obtain lipid and water-soluble fractions from the tumors. We also investigated effects on metastases and ascites formation. Pantethine treatment resulted in slower tumor progression, decreased levels of phosphocholine and phosphatidylcholine, and reduced metastases and ascites occurrence. In conclusion, pantethine represents a novel potential, well-tolerated, therapeutic tool in patients with ovarian cancer. Further in vivo preclinical studies are needed to confirm the beneficial role of pantethine and to better understand its mechanism of action.